2015
DOI: 10.1590/01000683rbcs20140393
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic Effectiveness and Competitiveness of Calopo Rhizobial Isolates in an Argissolo Vermelho-Amarelo Under Three Vegetation Covers in the Dry Forest Zone of Pernambuco

Abstract: Biological N fixation in forage legumes is an important alternative to reduce pasture degradation, and is strongly influenced by the inoculant symbiotic capability. This paper evaluates the effectiveness of Calopo (Calopogonium mucunoides) rhizobial isolated from soil under three vegetation covers of an Argissolo Vermelho-Amarelo of the Dry Forest Zone of Pernambuco. An experiment was conducted evaluating 25 isolates, aside from 5 uninoculated controls with 0; 309; 60; 90 and 120 kg ha -1 N, and a treatment in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
1
6
0
1
Order By: Relevance
“…The obtained results in our study showed that the native isolates presented symbiotic efficiency and better performance, ranging from 92 to 105%, in accordance with the reported by above mentioned authors. The best performance of native isolates compared with the recommended strains and the commercial inoculants has been reported in the literature (Calheiros et al, 2015) with calopogonium species, using isolates native to Northeast Brazil (84 to 131%). Menezes et al (2017) reported the the highest competitive potential among several rhizobia isolates by Erythrina velutina, which is native to Brazilian semiarid regions compared to the recommended strain.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The obtained results in our study showed that the native isolates presented symbiotic efficiency and better performance, ranging from 92 to 105%, in accordance with the reported by above mentioned authors. The best performance of native isolates compared with the recommended strains and the commercial inoculants has been reported in the literature (Calheiros et al, 2015) with calopogonium species, using isolates native to Northeast Brazil (84 to 131%). Menezes et al (2017) reported the the highest competitive potential among several rhizobia isolates by Erythrina velutina, which is native to Brazilian semiarid regions compared to the recommended strain.…”
Section: Discussionmentioning
confidence: 97%
“…However, L. leucocephala is an exotic legume species, native to Central America, and yet has nodulation in all soils, possibly due to the high promiscuity of this species, which is able to establish symbiosis with rhizobia of the genus Rhizobium (Pereyra et al, 2015), Mesorhizobium (Rangel et al, 2016), Sinorhizobium (Xu et al, 2014), Bradyrhizobium (Wang et al, 2006), and Cupriavidus (Florentino et al, 2009), Inoculation with native isolates of Rhizobia has significantly increased shoot biomass and symbiotic effectiveness compared to the recommended and noninoculated plants. The accumulation of nitrogen in shoot dry matter is normally used to estimate the symbiotic efficiency of nitrogen fixation of the native rhizobia according to Lima et al (2012) and Calheiros et al (2015). This method is easy to use and is relatively inexpensive.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the nodulation of cowpea with effective rhizobia may represent an important strategy to increase the interest to adopt the nitrogen fixation system. In recent years, the evaluation of effective rhizobia on various legumes have been increased and are conducted in the Brazilian Northeast with the promising results obtained for various legumes as described by Calheiros et al (2013Calheiros et al ( , 2015 for calopo; Lima et al (2012), for velvet beans, Torres Junior et al (2014) and Santos et al (2017) for peanuts, among others important species. However, few studies were carried out to evaluate the symbiotic effectiveness to increase cowpea yield by inoculation with specific strains of the Brazilian Northeast (Farias et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, prospecting of effective rhizobia for the inoculation of various legumes has been carried out in Brazilian soils, yielding promising results for calopo (Calheiros et al, 2013;Calheiros et al, 2015), velvet bean (Lima et al, 2012) and cowpea (Chagas Junior et al, 2010), among others. Nonetheless, few studies have evaluated the efficiency of peanut isolates (Hoffman et al, 2007;Torres Júnior et al, 2014;Sizenando et al, 2016).…”
Section: Introductionmentioning
confidence: 99%